Health effects among COVID-19 frontline health care professionals using level III personal protective equipment: A hospital-based descriptive study - Bindu, CM; Reena, R; Shyam, AC; Vivek, G; Chandrakala, C; Usha, SMR (Asian Journal of Medical Sciences, 2022)
Background: Global outbreak of deadly Corona virus disease has forced health care professionals of various disciplines in Hospital and community setting to use personal protective equipment (PPE) which consists of completely encapsulated suit, led the frontline health care professionals to face not only the physical discomfort but also other health consequences. Aims and Objectives: This study is conducted to assess the physical, physiological, and psychological health consequences faced by health care workers using Level III PPE when attending COVID-19 patients. Materials and Methods: This is a cross-sectional study conducted in the month of December 2020 and January 2021 amongst Medicos, Paramedicals, Nurses and other health care professionals in a tertiary care hospital attending COVID-19 duty using an online questionnaire which included sociodemographic profile, frequency of the duty, physical, physiological, psychological difficulties faced while using PPE, and the responses was recorded according to three-point Likert’s scale. Data were analyzed using suitable statistical methods with the help of SPSS V.23. Results: A total of227 front line warriors were included in the study with 157 (69%) males, 70 (31%) females among them 121 (53%) medicos, 68 (30%) nurses, 23 (10%) paramedicals, 15 (7%) others. Majority of them that is 186 were in 21–30 years age group, 31 in 31–40 years, 10 in >41 years. 124 (55%) used PPE for 4–6 h, 84 (37%) >6 h and 19 (8%) used for <4 h. Physical symptoms are most commonly faced health consequences followed by psychological and physiological symptoms. Medicos faced more difficulty and regularly in all three health consequences comparing with nurses and others. Conclusion: This study provides insight into various health consequences and difficulties experienced by the health care professionals while on PPE. Surveillance of the physical, physiological and psychological health consequences enroute us to prepare efficiently for future outbreaks worldwide.